Severity of Experimental Autoimmune Uveitis Is Reduced by Pretreatment with Live Probiotic Escherichia coli Nissle 1917 - Dusek, Otakar; Fajstova, Alena; Klimova, Aneta; Svozilkova, Petra; Hrncir, Tomas; Kverka, Miloslav; Coufal, Stepan; Slemin, Johan; Tlaskalova-Hogenova, Helena; Forrester, John V; Heissigerova, Jarmila (Cells, 2020)
Non-infectious uveitis is considered an autoimmune disease responsible for a significant burden of blindness in developed countries and recent studies have linked its pathogenesis to dysregulation of the gut microbiota. We tested the immunomodulatory properties of two probiotics, Escherichia coli Nissle 1917 (EcN) and E. coli O83:K24:H31 (EcO), in a model of experimental autoimmune uveitis (EAU). To determine the importance of bacterial viability and treatment timing, mice were orally treated with live or autoclaved bacteria in both preventive and therapeutic schedules. Disease severity was assessed by ophthalmoscopy and histology, immune phenotypes in mesenteric and cervical lymph nodes were analyzed by flow cytometry and the gut immune environment was analyzed by RT-PCR and/or gut tissue culture. EcN, but not EcO, protected against EAU but only as a live organism and only when administered before or at the time of disease induction. Successful prevention of EAU was accompanied by a decrease in IRBP-specific T cell response in the lymph nodes draining the site of immunization as early as 7 days after the immunization and eye-draining cervical lymph nodes when the eye inflammation became apparent. Furthermore, EcN promoted an anti-inflammatory response in Peyer's patches, increased gut antimicrobial peptide expression and decreased production of inducible nitric oxide synthase in macrophages. In summary, we show here that EcN controls inflammation in EAU and suggest that probiotics may have a role in regulating the gut-eye axis.
Keywords: Animals; Intestinal Mucosa; Probiotics; zánět; Female; Escherichia coli; Autoimmune Diseases; ženské pohlaví; Mice; mucosal immune system; myši; Inflammation; autoimunitní nemoci; uveitida; modely nemocí na zvířatech; probiotika; Uveitis; Disease Models, Animal; Escherichia coli Nissle 1917; macrophages; zvířata; probiotics; Mice, Inbred C57BL; experimental autoimmune uveitis; střevní sliznice; myši inbrední C57BL